An in vivo examination of the differences between rapid cardiovascular collapse and prolonged hypotension induced by snake venom - Rahini Kakumanu (Nature Portfolio, 2019)
Abstract We investigated the cardiovascular effects of venoms from seven medically important species of snakes: Australian Eastern Brown snake (Pseudonaja textilis), Sri Lankan Russell’s viper (Daboia russelii), Javanese Russell’s viper (D. siamensis), Gaboon viper (Bitis gabonica), Uracoan rattlesnake (Crotalus vegrandis), Carpet viper (Echis ocellatus) and Puff adder (Bitis arietans), and identified two distinct patterns of effects: i.e. rapid cardiovascular collapse and prolonged hypotension. P. textilis (5 µg/kg, i.v.) and E. ocellatus (50 µg/kg, i.v.) venoms induced rapid (i.e. within 2 min) cardiovascular collapse in anaesthetised rats. P. textilis (20 mg/kg, i.m.) caused collapse within 10 min. D. russelii (100 µg/kg, i.v.) and D. siamensis (100 µg/kg, i.v.) venoms caused ‘prolonged hypotension’, characterised by a persistent decrease in blood pressure with recovery. D. russelii venom (50 mg/kg and 100 mg/kg, i.m.) also caused prolonged hypotension. A priming dose of P. textilis venom (2 µg/kg, i.v.) prevented collapse by E. ocellatus venom (50 µg/kg, i.v.), but had no significant effect on subsequent addition of D. russelii venom (1 mg/kg, i.v). Two priming doses (1 µg/kg, i.v.) of E. ocellatus venom prevented collapse by E. ocellatus venom (50 µg/kg, i.v.). B. gabonica, C. vegrandis and B. arietans (all at 200 µg/kg, i.v.) induced mild transient hypotension. Artificial respiration prevented D. russelii venom induced prolonged hypotension but not rapid cardiovascular collapse from E. ocellatus venom. D. russelii venom (0.001–1 μg/ml) caused concentration-dependent relaxation (EC50 = 82.2 ± 15.3 ng/ml, Rmax = 91 ± 1%) in pre-contracted mesenteric arteries. In contrast, E. ocellatus venom (1 µg/ml) only produced a maximum relaxant effect of 27 ± 14%, suggesting that rapid cardiovascular collapse is unlikely to be due to peripheral vasodilation. The prevention of rapid cardiovascular collapse, by ‘priming’ doses of venom, supports a role for depletable endogenous mediators in this phenomenon.